Perioperative blood management programme reduces the use of allogenic blood transfusion in patients undergoing total hip and knee arthroplasty - Kopanidis, Paul (J Orthop Surg Res, 2016)
BACKGROUND: Optimisation of blood management in total hip (THA) and knee arthroplasty (TKA) is associated with improved patient outcomes. This study aimed to establish the effectiveness of a perioperative blood management programme in improving postoperative haemoglobin (Hb) and reducing the rate of allogenic blood transfusion. METHODS: This retrospective before and after study involves 200 consecutive patients undergoing elective TKA and THA before (Usual Care group) and after (Intervention group) the introduction of a blood management programme in an Australian teaching hospital. Patients in the Intervention group underwent preoperative treatment for anaemia and received intraoperative tranexamic acid (15 mg/kg). The primary outcomes were to compare postoperative Hb levels and the rate of blood transfusion. Secondary outcomes included measurements of total amount of allogenic blood transfused, transfusion-related complications, postoperative complications, need for inpatient rehabilitation and duration of hospital stay. RESULTS: There were no differences between baseline characteristics between groups. The mean (SD) preoperative Hb was higher in the Intervention group compared to that in the Usual Care group: 138.7 (13.9) vs. 133.4 (13.9) g/L, p = 0.008, respectively. The postoperative day 1 Hb, lowest postoperative Hb and discharge Hb were all higher in the Intervention group (p < 0.001). Blood transfusion requirements were lower in the Intervention group compared to the Usual Care group (6 vs. 20 %, p = 0.003). There were no differences in any of the secondary outcomes measured. Patients who were anaemic preoperatively and who underwent Hb optimisation had higher Hb levels postoperatively (odds ratio 5.7; 95 % CI 1.3 to 26.5; p = 0.024). CONCLUSIONS: The introduction of a perioperative blood optimisation programme improved postoperative Hb levels and reduced the rate of allogenic blood transfusion.